Nitric oxide is a ubiquitous signal for maintaining redox balance in plant cells: regulation of ascorbate peroxidase as a case study - Correa Aragunde, Maria Natalia (2015)
Oxidative and nitrosative stresses and their respective antioxidant responses are common metabolic adjustments operating in all biological systems. These stresses result from an increase in reactive oxygen species (ROS) and reactive nitrogen species (RNS) and an imbalance in the antioxidant response. Plants respond to ROS and RNS accumulation by increasing the level of the antioxidant molecules glutathione and ascorbate and by activating specific antioxidant enzymes. Nitric oxide (NO) is a free radical considered to be toxic or protective depending on its concentration, combination with ROS compounds, and subcellular localization. In this review we focus on the mechanisms of NO action in combination with ROS on the regulation of the antioxidant system in plants. In particular, we describe the redox post-translational modifications of cytosolic ascorbate peroxidase and its influence on enzyme activity. The regulation of ascorbate peroxidase activity by NO as a redox sensor of acute oxidative stress or as part of a hormone-induced signalling pathway leading to lateral root development is presented and discussed.